Postharvest Pathology of Fresh Horticultural Produce - Palou, Lluís; Smilanick, Joseph L. (Taylor & Francis Group, 2021)
Optimal distribution of fresh horticultural products entails prolonging their freshness and nutritional quality as long as possible after harvest. A major limitation to their marketing is decay after harvest, which is caused primarily by fungal pathogens. Postharvest Pathology of Fresh Horticultural Produce provides a comprehensive resource of information about the biology and control of postharvest diseases of many fresh horticultural products, citing sources from appropriate literature of any age, rather than only the most recent.